Anti-bacterial activity of dermcidin in human platelets: suppression of methicillin-resistant Staphylococcus aureus growth - Erxiong Liu; Shunli Gu; Weizhen Xi; Wenting Wang; Jinmei Xu; Ning An; Lingling Zhang; Jiajia Xin; Xingbin Hu; Yaozhen Chen; Qunxing An; Wen Yin (Microbiology Spectrum)
ABSTRACT Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most common drug-resistant bacteria that cause community and hospital infections. As one of the most common “superbugs” and the pathogen with the highest global incidence of hospital-acquired infections, MRSA has developed resistance to multiple antibiotics, posing a serious threat to public health. The rapid emergence and spread of multidrug resistance have increased the urgent need for new antimicrobial strategies and agents to combat MRSA-associated infections. In recent years, platelets have been widely recognized to play an important role in human immune defense. We have previously reported that platelets inhibit MRSA by inducing hydroxyl radical (OH●)-mediated apoptosis-like cell death. To further explore the platelet antibacterial mechanism, supernatants from co-culture of platelets and MRSA in vitro were used for proteomic analysis. Based on our observations using confocal and immunoelectron microscopy, we found a previously unrecognized platelet antimicrobial peptide, dermcidin (DCD), in the alpha (α-) granules. Furthermore, after co-culturing with MRSA in vitro, activated platelets secreted large amounts of DCD. Additionally, we confirmed that DCD displayed anti-MRSA activity in a concentration-dependent manner and contributed to the inhibition of MRSA growth by platelets in vitro. Our findings provide important insights into the immune defense functions of platelets.IMPORTANCEThe emerging multidrug resistance in many pathogenic bacterial species poses a serious problem worldwide. Methicillin-resistant Staphylococcus aureus (MRSA), one of the most common gram-positive pathogenic bacteria, has also evolved strains with multidrug resistance. This calls for the urgent development of novel and effective treatments or bactericidal agents to mitigate this issue in clinical settings. In this study, we identified for the first time a previously unrecognized platelet antimicrobial peptide, DCD, which impedes the proliferation of MRSA and promotes the antibacterial effect of platelets on MRSA. Our findings enrich our understanding of platelet physiological function and antibacterial mechanisms and provide new insights into the development of novel natural antimicrobial agents for controlling infections.